CHARACTERISTICS OF PRODUCTION OF RIVERS OF JIZZAK REGION (Web of Teachers: Inderscience Research, 2024)
The article talks about rivers, the formation of rivers, the role of natural conditions and natural geographical factors in their formation. In addition, based on the natural conditions of the Jizzakh region, the formation of natural hydrographic networks specific to the natural conditions was analyzed.